Analysis And Design Interoperability Of Spm Monitoring Data (Minimum Service Standard) Health Sector Cilacap Regency - Farid Mahmud (Jurnal Health Sains, 2023)
The Minimum Service Standards for the Health Sector (SPM-BK) cover provinces and regions, both of which have different service standards. In regional SPM-BK, there are 12 types of basic services that must be implemented, such as health services for pregnant women, mothers giving birth, newborns, toddlers, to health services for people at risk of contracting HIV. In its realization, SPM-BK regulates technical standards, which include standards for the quantity and quality of goods and/or services, health personnel/human resources, as well as technical instructions or procedures for providing the standards. Ideally, the performance achievement of the realization of local government SPM-BK is 100%. There are sharp differences in achievement covering both in one district at different times and between different districts/cities. Based on the analysis of the main constraints, a system is needed that can integrate MSS data from all health care facilities. The target is that the management information system (SIM) in health facilities can directly connect its data with the Komdat SPM application (Data Communication) Penelitian ini merupakan operational research menggunakan metode kualitatif dengan menerapkan perancangan sistem melalui tahapan System Development Life Cycle yang meliputi perencanaan, analisis, desain, dan implementasi. Perancangan interoperabilitas data pemonitoran SPM-BK dengan menggunakan metode RAD (Rapid Appplication Development) dengan pendekatan prototyping. Hasil wawancara mendalam dianalisis dengan menggunakan metode analisis isi (content analysis), yakni dengan dilakukan analisis komunikasi sistemik, obyektif, dan kuantitatif terhadap pesan yang terlihat. Data yang relevan dipilih dan tuangkan dalam bentuk narasi. Evaluasi sistem  yang digunakan dilakukan analisis deskriptif sebagai dasar analisis sistem interoperabiltas pemonitoran data SPM-BK.